IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER DI KOTA BANJAR - Nova Chalimah Girsang; , Riza Purnama; Eet Saeful Hidayat (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
At the implementation level, it turns out that there are still districts and cities that are constrained in developing the Gender Mainstreaming programme, this is because regional commitment is not yet strong so that the implementation of equitable Gender Mainstreaming is hampered. The purpose of this research is to analyse the implementation of the Gender Mainstreaming (PUG) policy in Kota Banjar. The research method uses a qualitative approach, which examines gender-responsive planning, gender-responsive programme implementation, and regulations that support gender-responsiveness. In the research, there are findings in the implementation of gender in Kota Banjar, including the PUG roadmap is not yet directed; It is not yet effective in supporting regional apparatus components; There is still a lack of understanding about PUG; Lack of planning system concepts; Lack of disaggregated data; Lack of monitoring. A comprehensive regional regulation is needed as a legal umbrella for the implementation of gender mainstreaming to strengthen and reinforce the existence of the performance of the PUG Technical Team and Working Group in Kota Banjar, improve PUG understanding, streamline the supporting components of regional apparatus, and so that the gender mainstreaming strategy in Kota Banjar becomes more effective.